Strategi Guru dalam Menghadapi Digitalisasi Pembelajaran di Madrasah Ibtidaiyah - Narsi, Narsi; Hidayati, Dian; Santosa, Achadi Budi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The world of education is undergoing a rapid transformation in the current digital era. This is due to the advancement of Information and Communication Technology (ICT), which brings major changes in various aspects of life, including the world of education. This research aims to describe teachers' strategies to deal with the digitalization of learning. The method used in this research is descriptive qualitative. This research was conducted at MI Muhammadiyah Plumbon, Eromoko sub-district with data collection techniques through interviews, observation and documentation. The results showed that the teacher's strategy to face the digitalization of learning was good. The strategies carried out include conducting various online trainings organized by the Ministry of Religion through the Smart Massive Online Open Course (MOOC), participating in the Teacher Working Group (KKG), conducting joint discussions with peers and collaborating with students of the UMS Informatics Engineering S1 study program to create learning media in the form of educational games. In addition to the above strategies, the awareness of teachers to continue to upgrade information about the digitalization of learning is also continuously carried out, with the spirit within themselves that continues to be maintained as a basic capital in facing the digitalization of learning.